Dystrophic Epidermolysis Bullosa: Secondary Disease Mechanisms and Disease Modifiers - Nyström, Alexander; Bruckner-Tuderman, Leena; Kiritsi, Dimitra (Frontiers in Genetics, 2021)
The phenotypic presentation of monogenetic diseases is determined not only by the nature of the causative mutations but is also influenced by manifold cellular, microenvironmental and external factors. Here, heritable extracellular matrix diseases, including dystrophic epidermolysis bullosa (DEB), are no exceptions. DEB is caused by mutations in the COL7A1 gene encoding collagen VII. Deficiency of collagen VII leads to skin and mucosal fragility, which progresses from skin blistering to severe fibrosis and cancer. Clinical and preclinical studies suggest that targeting of secondary disease mechanisms or employment of natural disease modifiers can alleviate DEB severity and progression. However, since many of these mechanisms are needed for tissue homeostasis, informed, selective targeting is essential for safe and efficacious treatment. Here, we discuss a selection of key disease modifiers and modifying processes active in DEB, summarize the still scattered knowledge of them and reflect on ways forward toward their utilization for symptom-relief or enhancement of curative therapies.